GPER‐induced signaling is essential for the survival of breast cancer stem cells. Issue 6 (7th August 2019) - Chan, Yu‐Tzu; Lai, Alan C.‐Y.; Lin, Ruey‐Jen; Wang, Ya‐Hui; Wang, Yi‐Ting; Chang, Wen‐Wei; Wu, Hsin‐Yi; Lin, Yu‐Ju; Chang, Wen‐Ying; Wu, Jen‐Chine; Yu, Jyh‐Cherng; Chen, Yu‐Ju; et al.
Abstract : G protein‐coupled estrogen receptor‐1 (GPER), a member of the G protein‐coupled receptor (GPCR) superfamily, mediates estrogen‐induced proliferation of normal and malignant breast epithelial cells. However, its role in breast cancer stem cells (BCSCs) remains unclear. Here we showed greater expression of GPER in BCSCs than non‐BCSCs of three patient‐derived xenografts of ER − /PR + breast cancers. GPER silencing reduced stemness features of BCSCs as reflected by reduced mammosphere forming capacity in vitro, and tumor growth in vivo with decreased BCSC populations. Comparative phosphoproteomics revealed greater GPER‐mediated PKA/BAD signaling in BCSCs. Activation of GPER by its ligands, including tamoxifen (TMX), induced phosphorylation of PKA and BAD‐Ser118 to sustain BCSC characteristics. Transfection with a dominant‐negative mutant BAD (Ser118Ala) led to reduced cell survival. Taken together, GPER and its downstream signaling play a key role in maintaining the stemness of BCSCs, suggesting that GPER is a potential therapeutic target for eradicating BCSCs. Abstract : What's new? G protein‐coupled estrogen receptor‐1 (GPER) mediates estrogen‐induced proliferation of normal and malignant breast epithelial cells. However, the role of GPER in breast cancer stem cells (BCSC) biology remains unclear. Here, using patient‐derived xenografts of ER–/PR+ breast cancer, the authors found higher expression of GPER in BCSCs than non‐BCSCs. Moreover, the results indicated that stemness features were sustained via GPER‐mediated PKA/BAD phosphorylation. Stimulation by the GPER ligand tamoxifen enhanced BCSC cell viability and population and BAD phosphorylation. The findings revealed a vital role of GPER‐mediated signaling pathways in BCSC survival, suggesting GPER as a potential therapeutic target for eradicating BCSCs.